Antimicrobial activity of kombucha drink made of kecombrang flowers (Etlingera elatior) towards pathogens - Raihana, Shafa' Assyifa; Emmawati, Aswita (Journal of Tropical AgriFood, 2026)
Kombucha is a functional drink with benefits for human health, including antimicrobial activity. It could be made from torch ginger, an Indonesian tropical plant that is known as a vegetable and ornamental plant and has antimicrobial activity against pathogens. This study aimed to determine the effect of fermentation time and sugar content of kombucha made from torch ginger flowers on antimicrobial activity against pathogens. The research was conducted with two treatments: 20, 25, and 30% (w/v) sugar addition and 7, 14, and 21 days of fermentation. The antimicrobial activity of the kombucha drink made from 12% torch ginger was evaluated using the well diffusion method. The test pathogens were Escherichia coli ATCC 11775, Bacillus cereus ATCC 11778, Staphylococcus aureus ATCC 33591, and Salmonella typhi ATCC 14028. The results showed that torch ginger kombucha with 20% sugar and fermented for 14 days significantly inhibited Staphylococcus aureus ATCC 33591 and Bacillus cereus ATCC 11778. The Minimum Inhibitory Concentration (MIC) against both pathogens was observed in 20% kombucha. Therefore, kombucha made from torch ginger has the potential to be an antimicrobial against pathogens.